Engineered Vascularized Flaps, Composed of Polymeric Soft Tissue and Live Bone, Repair Complex Tibial Defects (Adv. Funct. Mater. 44/2021). (26th October 2021) - Redenski, Idan; Guo, Shaowei; Machour, Majd; Szklanny, Ariel; Landau, Shira; Kaplan, Ben; Lock, Roberta I.; Gabet, Yankel; Egozi, Dana; Vunjak‐Novakovic, Gordana; Levenberg, Shulamit
Abstract : Engineered Vascularized Flaps In article number 2008687, Shulamit Levenberg and co‐workers fabricate composite neo‐tissue flaps by combining polymeric matrices and decellularized bone. These are perfused in vivo using hosts via a potent neo‐vascular network. In vivo imaging is utilized to show how composite flaps support long‐term bone repair and vascularization. This methodology may one day replace autologous tissue harvest from patients in need of tissue replacements.